Development of Dyslexia: The Delayed Neural Commitment Framework - Nicolson, Roderick I.; Fawcett, Angela J. (Frontiers in Behavioral Neuroscience, 2019)
It is now evident that explanations of many developmental disorders need to include a network perspective. In earlier work, we proposed that developmental dyslexia is well-characterised in terms of impaired procedural learning within the language networks, with the cerebellum being the key structure involved. Here we deepen the analysis to include the child’s developmental process of constructing these networks. The ‘delayed neural commitment’ framework proposes that, in addition to slower skill acquisition, dyslexic children take longer to build (and to rebuild) the neural networks that underpin the acquisition of reading. The framework provides an important link backwards in time to the development of executive function networks, and the earlier development of networks for language and speech. It is consistent with many theories of dyslexia, while providing fruitful suggestions for further research at the genetic, brain, cognitive and behavioural levels of explanation. It also has significant implications for assessment and teaching.